Dynamics of Turning Operation Part I: Experimental Analysis Using Instantaneous Frequency - Halfmann, Eric B.; Suh, C. Steve; Hung, Wayne N.P. (Journal of Vibration Testing and System Dynamics, 2026)
The workpiece and tool vibrations on a lathe are experimentally stud- ied to establish improved understanding of cutting dynamics that would support efforts in exceeding the current limits of the turning process. A Keyence laser displacement sensor is employed to monitor the workpiece and tool vibrations during chatter-free and chatter cut- ting. A procedure is developed that utilizes instantaneous frequency (IF) to identify the modes related to measurement noise and those innate of the cutting process. It is found that IF thoroughly charac- terizes the underlying turning dynamics and identifies the exact time when chatter is fully developed. That IF provides the needed reso- lution for identifying the onset of chatter suggests that the stability of the process should be monitored in the time-frequency domain to effectively detect and characterize machining instability. It is deter- mined that for the cutting tests performed chatter of the workpiece and tool are associated with the changing of the spectral components and more specifically period-doubling bifurcation.